Molecular pharmacology of Caenorhabditis elegans serotonin-gated chloride channel mod-1 as a novel drug target for anthelmintic therapy - Rodriguez Araujo, Noelia (2020)
Serotonin-gated ion channels (5-HT3 ) belong to the family of Cys- loop receptors, which are pentameric proteins that mediate fast syn- aptic transmission. In mammals, 5-HT3 are non-selective cationic channels that can be homomeric (5-HT3 A) or heteromeric. Caenor- habditis elegans is a model for the study of the nervous system and for antiparasitic drug discovery. As parasitic nematodes, C. el- egans contains a homomeric 5HT-gated chloride channel, MOD-1, that modulates locomotory behavior. Due to its absence in verte- brates, MOD-1 emerges as a potential antiparasitic drug target. We deciphered its pharmacological properties and searched for novel ligands by patch clamp recordings from mammalian cells heterolo- gously expressing MOD-1. Macroscopic currents activated by 5-HT showed that MOD-1 does not rectify, desensitizes slowly, and re- covers from desensitization with a time constant of 1 s. Dose-re- sponse curves revealed an EC50 for 5-HT of about 1 μM, similar to that of human 5-HT3 A receptors. However, compared to their actions as partial agonists of human 5-HT3 A receptors, tryptamine showed markedly increased efficacy and 2-Me-5HT showed insig- nificant agonist activity at MOD-1. The typical anthelmintic drugs ivermectin (IVM), levamisole, and piperazine, which are agonists of GluCl, L-AChR and GABA receptors, respectively, did not activate MOD-1. However, IVM produced a slight and piperazine a profound inhibition of 5-HT activated MOD-1 currents. The analysis revealed that piperazine is a noncompetitive antagonist of MOD-1. To gain further insights into the molecular function of the native MOD-1, we also recorded 5HT-activated chloride channels from C. elegans neurons expressing MOD-1 and compared to those heterologous- ly expressed in mammalian cells. The elucidation of the molecular pharmacology of MOD-1 contributes to our knowledge of the func- tion and drug selectivity of Cys-loop receptors and to its potential as a novel target for anthelmintic therapy.